Z(2) SIMP dark matter - Bernal, Nicolas [UNESP]; Chu, Xiaoyong (Iop Publishing Ltd, 2016)
Dark matter with strong self-interactions provides a compelling solution to several small-scale structure puzzles. Under the assumption that the coupling between dark matter and the Standard Model particles is suppressed, such strongly interacting massive particles (SIMPs) allow for a successful thermal freeze-out through N-to-N' processes, where N dark matter particles annihilate to N' of them. In the most common scenarios, where dark matter stability is guaranteed by a Z(2) symmetry, the seemingly leading annihilating channel, i.e. 3-to- 2 process, is forbidden, so the 4-to-2 one dominate the production of the dark matter relic density. Moreover, cosmological observations require that the dark matter sector is colder than the thermal bath of Standard Model particles, a condition that can be dynamically generated via a small portal between dark matter and Standard Model particles, a la freeze-in. This scenario is exempli fied in the context of the Singlet Scalar dark matter model.
Keywords: dark matter theory; particle physics - cosmology connection